(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2011)
Two coral species from the Early Aptian of the Monti d’Ocre area (Abruzzi) originally assigned to the genus Microsaraea Koby, 1889 are revised on the basis of their type material. Both are assigned to the genus Polyphylloseris. They are considered synonymous. The senior synonym, Microsaraea distefanoi Prever, 1909, was formerly assigned to the genus Microsolena and has a wide geographical and stratigraphical distribution. Since Microsaraea distefanoi Prever belongs to a different genus, the citations in the literature of this species are critically reviewed and, where possible, assigned to the proper Microsolena species.